An Equivalent Substitute Strategy for Constructing 3D Ordered Porous Carbon Foams and Their Electromagnetic Attenuation Mechanism - Zhang, Meng; Ling, Hailong; Wang, Ting; Jiang, Yingjing; Song, Guanying; Zhao, Wen; Zhao, Laibin; Cheng, Tingting; Xie, Yuxin; Guo, Yuying; Zhao, Wenxin; Yuan, Liying; et al. (Nano-Micro Letters, 2022)
Three-dimensional (3D) ordered porous carbon is generally believed to be a promising electromagnetic wave (EMW) absorbing material. However, most research works targeted performance improvement of 3D ordered porous carbon, and the specific attenuation mechanism is still ambiguous. Therefore, in this work, a novel ultra-light egg-derived porous carbon foam (EDCF) structure has been successfully constructed by a simple carbonization combined with the silica microsphere template-etching process. Based on an equivalent substitute strategy, the influence of pore volume and specific surface area on the electromagnetic parameters and EMW absorption properties of the EDCF products was confirmed respectively by adjusting the addition content and diameter of silica microspheres. As a primary attenuation mode, the dielectric loss originates from the comprehensive effect of conduction loss and polarization loss in S-band and C band, and the value is dominated by polarization loss in X band and Ku band, which is obviously greater than that of conduction loss. Furthermore, in all samples, the largest effective absorption bandwidth of EDCF-3 is 7.12 GHz under the thickness of 2.13 mm with the filling content of approximately 5 wt%, covering the whole Ku band. Meanwhile, the EDCF-7 sample with optimized pore volume and specific surface area achieves minimum reflection loss (RLmin) of − 58.08 dB at 16.86 GHz while the thickness is 1.27 mm. The outstanding research results not only provide a novel insight into enhancement of EMW absorption properties but also clarify the dominant dissipation mechanism for the porous carbon-based absorber from the perspective of objective experiments. Highlights: 1 Three-dimensional ordered porous carbon foam with abundant hetero-atoms is successfully prepared through employing silica microspheres template. 2 The pore volume and specific surface area are effectively adjusted by an equivalent substitute strategy to investigate their influence on electromagnetic wave absorption performances. 3 The attenuation mechanism of electromagnetic wave is clarified according to the contribution of conduction loss and polarization loss on dielectric loss.